HUBUNGAN KETERSEDIAAN AIR TANAH DAN SIFAT-SIFAT DASAR FISIKA TANAH - Kukuh Murtilaksono; Enny Dwi Wahyuni (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2004)
This research was conducted to study the relationship between soil moisture content and soil physical characteristics that affected the moisture.The soil samples were collected from 22 scattered sites of West Java and Central Java. Analysis of soil physical properties (texture, bulk density, particle density, total porosity and soil moisture retention) and soil chemical property (organic matter) was conducted at the laboratory of the Department of Soil Sciences, Faculty of Agriculture, Bogor Agricultural University. Analysis of simple linear regression was applied to know the correlation between soil moisture content and other basic soil physical properties.Availability of soil moisture (pF 4.20 – pF 2.54) significantly correlated with organic matter, total porosity, and micropores. The higher organic matter content, as well as total porosity and micro, pores the higher available soil moisture. Soil moisture of field capacity significantly correlated with clay content, sand content, micro and macropores. The higher clay content and micropores the higher soil moisture of field capacity. In the contrary, the higher macropores and sand content the lower the field capacity. Soil moisture of the wilting point significantly correlated with clay content and macropores. The higher clay content the higher the wilting point, while the higher macro pores the lower soil moisture of wilting point. Keywords: Available soil water, field capacity, organic matter, soil pores, wilting point